When TADs go bad: chromatin structure and nuclear organisation in human disease [version 1; referees: 2 approved] - Vera B Kaiser (F1000Research, 2017)
Chromatin in the interphase nucleus is organised as a hierarchical series of structural domains, including self-interacting domains called topologically associating domains (TADs). This arrangement is thought to bring enhancers into closer physical proximity with their target genes, which often are located hundreds of kilobases away in linear genomic distance. TADs are demarcated by boundary regions bound by architectural proteins, such as CTCF and cohesin, although much remains to be discovered about the structure and function of these domains. Recent studies of TAD boundaries disrupted in engineered mouse models show that boundary mutations can recapitulate human developmental disorders as a result of aberrant promoter-enhancer interactions in the affected TADs. Similar boundary disruptions in certain cancers can result in oncogene overexpression, and CTCF binding sites at boundaries appear to be hyper-mutated across cancers. Further insights into chromatin organisation, in parallel with accumulating whole genome sequence data for disease cohorts, are likely to yield additional valuable insights into the roles of noncoding sequence variation in human disease.